Unveiling The Hidden Depths: A Deep Dive into Conversational Implicature In 'Lone Survivor' Directed by Peter Berg - Wahyu Utomo, Dhafid; Sidik , Ezis Japar; Mayasari, Jalia (Indo-MathEdu Intellectuals Journal, 2024)
This research delves into the nuanced world of conversational implicature, exploring the implied meanings and flouts of Grice’s cooperative principle in the film "Lone Survivor" directed by Peter Berg. Utilizing a descriptive qualitative method, this study focuses on specific dialogues to identify instances of maxim flouts and to unravel their underlying implications. Grice’s theory provides the analytical framework for this investigation. Moreover, content analysis technique was used to analyze the data. The findings reveal multiple flouts of the maxims of quality, quantity, relevance, and manner, each leading to various implied meanings. These flouts not only shed light on the intricacies of human communication but also offer a unique perspective on character dynamics and narrative development within the film. Ultimately, this study enriches our understanding of conversational implicature in cinematic discourse, highlighting the complexities of communication in narrative storytelling and underscoring the importance of context in interpreting meaning